Influence of light exposure during early life on the age of onset of bipolar disorder. (May 2015) - Bauer, Michael; Glenn, Tasha; Alda, Martin; Andreassen, Ole A.; Angelopoulos, Elias; Ardau, Raffaella; Baethge, Christopher; Bauer, Rita; Baune, Bernhard T.; Bellivier, Frank; Belmaker, Robert H.; Berk, Michael; et al.
Abstract: Background: Environmental conditions early in life may imprint the circadian system and influence response to environmental signals later in life. We previously determined that a large springtime increase in solar insolation at the onset location was associated with a younger age of onset of bipolar disorder, especially with a family history of mood disorders. This study investigated whether the hours of daylight at the birth location affected this association. Methods: Data collected previously at 36 collection sites from 23 countries were available for 3896 patients with bipolar I disorder, born between latitudes of 1.4 N and 70.7 N, and 1.2 S and 41.3 S. Hours of daylight variables for the birth location were added to a base model to assess the relation between the age of onset and solar insolation. Results: More hours of daylight at the birth location during early life was associated with an older age of onset, suggesting reduced vulnerability to the future circadian challenge of the springtime increase in solar insolation at the onset location. Addition of the minimum of the average monthly hours of daylight during the first 3 months of life improved the base model, with a significant positive relationship to age of onset. Coefficients for all other variables remained stable, significant and consistent with the base model. Conclusions: Light exposure during early life may have important consequences for those who are susceptible to bipolar disorder, especially at latitudes with little natural light in winter. This study indirectly supports the concept that early life exposure to light may affect the long term adaptability to respond to a circadian challenge later in life. Highlights: Large spring increase in sunlight associated with younger onset of bipolar I disorder. We studied the impact of hours of daylight during early life (first 6 months) on this association (N = 3215). More daylight in the first 3 months of early life associated with older onset. Human circadian system still developing during early life. Early life light exposure may affect vulnerability to future circadian challenges.